AGROECOLOGY AND FOOD SECURITY: STRATEGIES FOR INTEGRATING ECOLOGICAL PRINCIPLES INTO GLOBAL AGRICULTURAL SYSTEMS - Almira Ulimaz; Sevda Kara; Murat Arslan (Techno Agriculturae Studium of Research, 2026)
Global food systems are facing increasing challenges arising from climate change, biodiversity loss, land degradation, resource depletion, and growing food demand. Conventional agricultural models have succeeded in enhancing productivity but have often generated environmental consequences that threaten long-term food security and ecological sustainability. Agroecology has emerged as a promising framework that applies ecological principles to agricultural production systems while promoting resilience, biodiversity conservation, and sustainable resource management. This study aims to examine the role of agroecology in strengthening food security and to identify strategies for integrating ecological principles into global agricultural systems. A qualitative research design based on a systematic literature review and thematic analysis was employed. Data were collected from peer-reviewed journal articles, international policy reports, institutional publications, and empirical studies published between 2010 and 2025. Findings indicate that agroecological practices contribute significantly to food security by improving soil fertility, enhancing biodiversity, increasing climate resilience, reducing dependence on external inputs, and strengthening local food systems. Community participation, knowledge integration, institutional support, and ecological diversification emerged as critical factors influencing successful implementation. Agroecological systems demonstrated greater adaptability to environmental and socio-economic disturbances compared with conventional agricultural approaches. The study concludes that integrating ecological principles into agricultural systems provides a viable pathway for achieving sustainable food security while simultaneously promoting environmental stewardship, agricultural resilience, and long-term sustainability within global food systems.